IDEOLOGI PENCAPRESAN TAHUN 2024 PADA MEDIA DIGITAL DI INDONESIA: PERSPEKTIF TEUN A. VAN DIJK - Minto, Deri Wan; Anshori, Dadang S.; Damaianti, Vismaia S.; Sastromiharjo, Andoyo; Zulfadhli, Muhammad (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
News of the 2024 presidential election has begun to emerge through mass media, especially in digital media. With the digitization, the development of news has become so fast. Without realizing it, this progress can be eroded by the flow of information that is always dynamic. News must be of character and quality. Journalists must always have their own strategies, tactics, and moves in creating ideology to the audience through published news texts. This study principally aims to describe the ideology of the 2024 presidential bid on digital media in Indonesia: Teun A. van Dijk's perspective which focuses on digital media Kompas.com. The sample in this study is 5 news published in April-May with the theme